IMPLEMENTASI FRACTIONAL BROWNIAN MOTION DENGAN PARAMETER HURST UNTUK DATA PAJAK HOTEL - Nugroho, Samuel Defri; Mariani, Scolastika (Universitas Negeri Semarang, 2016)
Fractional Brownian Motion (FBM) is general Brownian Motion (BM) that impact for construction tax hotel, this can instrument for decision. the trouble is how to do value best implementation estimate FBM and BM with Hurst parameter for tax hotel. How to do impact matlab program for that. data can uses is data tax hotel in Semarang. Purpose research is know value estimate FBM and BM and impact that with matlab program. Process construction is input Hurst [0,1], Î”t, and N to estimate Hurst output value estimate, this value input to FBM and BM (H=0.5) process, output this value construction finance for covarians Hurst and bias Hurst for finaly value RMSE (Root Mean Square Error).